PENGARUH WADAH MEMASAK YANG BERBEDA TERHADAP SIFAT FISIKO-KIMIA DAGING AYAM MASAK BUMBU RINTEK WUUK (RW) - Yusuf, Sri Hardiastuti; Rompis, John E.G.; Tinangon, Meilani R.; Sondakh, E.H.B. (Universitas Sam Ratulangi, 2020)
THE INFLUENCES OF DIFFERENT COOKING POT ON THE PHYSIC-CHEMICAL PROPERTIES OF THE TRADITIONAL â€œRINTEK WUUK (RW)â€ SEASONING CHICKEN. This research was done to evaluate the influence of cooking methods with different containers on physic-chemical properties (pH, water holding capacity, and cooking losses) of chicken meat seasoning traditional â€œrintek wuuk (RW)â€. The research was conducted using complete random draft (CRD) through three container treatment (bamboo, ground and frying pan) using RW traditional seasoning. The physic-chemical properties were analyzed in animal science technology laboratory. Data analysis used analysis of variance (ANOVA). Results of this study showed that different cooking containers did not affect the physic-chemical properties of seasoning RW chicken meat. These results can be concluded that the use of different containers did not give a real influence on the physic-chemical properties of the seasoning RW chicken meat.Â Keywords: Chicken meat, cooking container, RW seasoning, Physic-chemical properties.Â Â Â Â Â Â Â Â